TINGKAT KEPUASAN IBU TENTANG MUTU PELAYANAN POSYANDU BALITA (Studi deskriptif di Posyandu Balita Dusun Sambiroto Desa Sambirobyong Kecamatan Kayen Kidul Kabupaten Kediri Tahun 2014) - Sukatmi, Sukatmi; Wulansari, Yuni (Akademi Keperawatan Pamenang, 2014)
Mother satisfaction towards service quality in health care center for mothers and babies (Posyandu) is influenced by many factors real evidence (tangible), reliability (reliability/trustworthy), responsiveness and assurance (certainty). These things must be fulfilled by officials or cadres of health care center for mothers and babies (Posyandu) in order to satisfied all targets. The purpose of this research was to know the level of mother satisfaction about the quality of health care center for mothers and babies (Posyandu) health services in Posyandu Dusun Sambiroto Desa Sambirobyong Kecamatan Kayen Kidul Kabupaten Kediri.The design of research that used is descriptive. The population is all the mothers of babies that exist in health care center for mothers and babies (Posyandu) with the total 30 mothers with sample 30 respondents was taken with a total sampling technique. Research variable is the level of satisfaction about quality of health care center for mothers and babies (Posyandu) health services collected by using questionnaire with the total 25 questions. The data that produced is processed by means of editing, cording, scoring, tabulating and analyzed by percentage. The data presented in the form of diagrams and tables.From the results of research, in general most of the respondents are satisfied about 21 respondents (70 %), very satisfied 8 respondents (26.7%) or fairly satisfied 1 respondent (3.3%) of a total of 30 respondents.Â This is caused by physique facilities of health care center for mothers and babies (Posyandu) are adequate, the officer gave service with a friendly, courteous, responsive, professional and reliable.It was concluded that the quality of service in Posyandu Dusun Sambiroto Desa Sambirobyong Kecamatan Kayen Kidul Kabupaten Kediri has been rated satisfactory. It is suggested that existing services must be maintained.Â Keywords : satisfaction, service quality of Balita Posyandu